The Idiot - Dostoevsky, Fyodor (Wordsworth Editions Ltd, 1996)
Prince Myshkin returns to Russia from an asylum in Switzerland. As he becomes embrolled in the frantic amatory and financial intrigues which centre around a cast of brilliantly realised characters and which ultimately lead to tragedy, he emerges as a unique combination of the Christian ideal of perfection and Dostoevsky's own views, affiction and manners...
Keywords: Fiction